(untitled) (Revista Medica de los Postgrados de Medicina, 2012)
Palabras Clave: TDAH; Reprobación Escolar; nutrición DOI: http://dx.doi.org/10.5377/rmpm.v13i3.631 Revista de los Postgrados de Medicina UNAH Vol. 13 N° 3 Agosto-Octubre 2010